b n introduction /c - Furr, R. Michael (Los Angeles : Sage, 2018)
In An Introduction , R. Michael Furr centres his presentation of material around a conceptual understanding of psychometric issues, such as validity and reliability, and on purpose rather than procedure, the "why" rather than the "how to." By emphasizing concepts over mathematical proofs and by focusing on practical significance, this book assists students in appreciating not just how measurement problems can be addressed, but why it is important to address them.
Includes references and index.
Keywords: Psychometrics